Comparison of Sn-5Sb and Sn-10Sb Alloys in Tensile and Fatigue Properties Using Miniature Size Specimens. (13th June 2018) - Kobayashi, Tatsuya; Kobayashi, Kyosuke; Mitsui, Kohei; Shohji, Ikuo
Abstract : Tensile and low cycle fatigue properties of Sn-5Sb (mass%) and Sn-10Sb (mass%) were investigated using miniature size specimens, and fracture behaviors of the specimens were observed. Tensile strength and 0.1% proof stress of both alloys decrease with increasing the temperature. The tensile strength and 0.1% proof stress of Sn-10Sb are higher than those of Sn-5Sb at 25°C. Elongation of Sn-5Sb decreases with increasing the temperature except for a strain rate of 2 × 10 −1  s −1, while Sn-10Sb increases with increasing temperature. Although elongation of Sn-10Sb is lower than that of Sn-5Sb at 25°C, the difference between them is small at 150°C. Chisel-point fracture was observed in both alloys regardless of conditions of the tensile test. The low cycle fatigue lives of Sn-5Sb and Sn-10Sb alloys obey the Manson–Coffin equation, and the fatigue ductility exponent, α, was 0.54 for Sn-5Sb and 0.46 for Sn-10Sb in the temperature range from 25°C to 150°C. On the basis of the observation of fractured specimens and the investigation of α, it was clarified that the crack progress can be delayed by the formation of coarse SbSn compounds in the Sn-Sb alloy, and thus the fatigue properties can be improved.